2020
DOI: 10.3390/nu12030761
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids and Other Polyphenols Act as Epigenetic Modifiers in Breast Cancer

Abstract: Breast cancer is a common cancer that occurs due to different epigenetic alterations and genetic mutations. Various epidemiological studies have demonstrated an inverse correlation between breast cancer incidence and flavonoid intake. The anti-cancer action of flavonoids, a class of polyphenolic compounds that are present in plants, as secondary metabolites has been a major topic of research for many years. Our review analysis demonstrates that flavonoids exhibit anti-cancer activity against breast cancer occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(88 citation statements)
references
References 99 publications
0
67
0
Order By: Relevance
“…Several studies have demonstrated the action of resveratrol in modulating DNA methylation in several genes involved in cancer (72). In a recent study, resveratrol was shown to restore the hypomethylated and hypermethylated state of key tumor-suppressor and oncogenic genes, respectively (73). In that study, methylation alterations were consistent with changes in mRNA expression.…”
Section: Nutraceuticals and Gene Expressionmentioning
confidence: 76%
“…Several studies have demonstrated the action of resveratrol in modulating DNA methylation in several genes involved in cancer (72). In a recent study, resveratrol was shown to restore the hypomethylated and hypermethylated state of key tumor-suppressor and oncogenic genes, respectively (73). In that study, methylation alterations were consistent with changes in mRNA expression.…”
Section: Nutraceuticals and Gene Expressionmentioning
confidence: 76%
“…Hence, research on an alternative approach to treat cancer without side effects is in high demand. Few natural products like flavonoids and polyphenols have better anticancer activity [24]. In silico molecular docking study revealed that rutin has higher binding affinity to both over-expressed ALDH1A3 and ALDH18A1 gene among 12 selected natural compounds.…”
Section: Discussionmentioning
confidence: 99%
“…It's well-proved that the epigenetic changes, besides genetic alteration, are involved in cancer development. According to recent studies, flavonoid components such as kaempferol, quercetin, and catechin can modify the epigenetic alteration involved in the tumorogenesis process (26,27).…”
Section: Discussionmentioning
confidence: 99%